Optimized hyperventilation preserves 2,3-diphosphoglycerate in severe traumatic brain injury A hiperventilação otimizada preserva o 2,3-difosfoglicerato no traumatismo craniencefálico grave - Rayne Borges Torres; Renato Giuseppe Giovanni Terzi; Antônio Luís Eiras Falcão; Nelci Fenalti Höehr; Venâncio Pereira Dantas Filho (Arquivos de Neuro-Psiquiatria)
INTRODUCTION: The concentration of 2,3-diphosphoglycerate (2,3-DPG/Hct) increases as a physiological occurrence to pH increase and hyperventilation. This response was tested in patients with severe traumatic brain injury (TBI). METHOD: The concentration of 2,3-DPG/Hct was measured daily for six days in eleven patients with severe TBI in need of optimized hyperventilation because of intracranial hypertension. RESULTS:There was correlation between pH and the concentration of DPG/Hct. The concentration of 2,3-DPG/Hct remained predominantly within normal levels with slight increase in the sixth day of the study. The concentration of 2,3-DPG/Hct correlated significantly with measured partial pressure of oxygen that saturates 50% the hemoglobin of the blood (P50st), confirming the consistency of our data. CONCLUSION: The expected physiological response of a progressive increase in concentration of 2,3-DPG/Hct to hyperventilation was not observed. This fact may be explained by the intermittent and not sustained hyperventilation as dictated by the protocol of optimized ventilation. INTRODUÇÃO: A concentração de 2,3-difosfoglicerato nos eritrócitos (2,3-DPG/Hct) aumenta como ocorrência fisiológica ao aumento do pH e à hiperventilação. Esta resposta foi testada em pacientes com traumatismo craniencefálico (TCE) grave. MÉTODO: A concentração de 2,3-DPG/Hct foi medida diariamente, durante seis dias, em 11 pacientes com TCE grave necessitando de hiperventilação otimizada por causa da hipertensão intracraniana. RESULTADOS: Houve correlação entre o pH e a concentração de 2,3-DPG/Hct. A concentração de 2,3-DPG/Hct permaneceu predominantemente dentro da normalidade, com ligeira tendência à elevação no sexto dia de estudo. Houve correlação entre a concentração de 2,3-DPG/Hct e a pressão parcial de oxigênio que satura 50% da hemoglobina (P50st), confirmando a consistência dos dados. CONCLUSÃO: A esperada resposta fisiológica de aumento progressivo da concentração de 2,3-DPG/Hct não foi observada. Este fato pode ser explicado pela aplicação intermitente e não sustentada de hiperventilação, como ditado pelo protocolo clínico de ventilação otimizada.